mTORC1 Signaling Pathway Mediates Chronic Stress-Induced Synapse Loss in the Hippocampus - Luo, Yu-Fei; Ye, Xiao-Xia; Fang, Ying-Zhao; Li, Meng-Die; Xia, Zhi-Xuan; Liu, Jian-Min; Lin, Xiao-Shan; Huang, Zhen; Zhu, Xiao-Qian; Huang, Jun-Jie; Tan, Dong-Lin; Zhang, Yu-Fei; et al. (Frontiers in Pharmacology, 2021)
Background: The mammalian target of rapamycin (mTOR) signaling has served as a promising target for therapeutic intervention of major depressive disorder (MDD), but the mTOR signaling underlying MDD has not been well elucidated. In the present study, we investigated whether mTOR signaling pathway mediates synapse loss induced by chronic stress in the hippocampus. Methods: Chronic restraint stress-induced depression-like behaviors were tested by behavior tests (sucrose preference test, forced swim test and tail suspension test). Synaptic proteins and alternations of phosphorylation levels of mTOR signaling-associated molecules were measured using Western blotting. In addition, mRNA changes of immediate early genes (IEGs) and glutamate receptors were measured by RT-PCR. Results: After successfully establishing the chronic restraint stress paradigm, we observed that the mRNA levels of some IEGs were significantly changed, indicating the activation of neurons and protein synthesis alterations. Then, there was a significant downregulation of glutamate receptors and postsynaptic density protein 95 at protein and mRNA levels. Additionally, synaptic fractionation assay revealed that chronic stress induced synapse losses in the dorsal and ventral hippocampus. Furthermore, these effects were associated with the mTOR signaling pathway-mediated protein synthesis, and subsequently the phosphorylation of associated downstream signaling targets was reduced after chronic stress. Finally, we found that intracerebroventricular infusion of rapamycin simulated depression-like behavior and also blocked the antidepressant effects of fluoxetine. Conclusion: Overall, our study suggests that mTOR signaling pathway plays a critical role in mediating synapse loss induced by chronic stress, and has part in the behavioral effects of antidepressant treatment.